The use of hyperoxia as a way to accelerate recovery after a karate and judo match - Pupis, M.; Sližik, M.; Bartik, P. (Journal of Human Sport & Exercise, 2013)
The research study is concerned with the use of hyperoxia (an abnormally increased supply or concentration of oxygen) as a possible way to accelerate recovery time after anaerobic load in karate and judo. The study sample consisted of 23 top athletes (14 karatekas, 9 judokas) aged 22 to 29. All these athletes inhaled a hyperoxic gas mixture (containing 95 ± 4% of oxygen in the inhaled air) or a placebo (air) from an oxygen concentrator before and after the match. Lactate level was measured in the third and 10th minute after the match. Following the match before which the athletes had inhaled the concentrated oxygen, the average lactate level was 10.44 (SD 2.76) mmol/L. On the other hand, the lactate level after the match before which they had inhaled placebo equalled 10.43 (SD 2.92) mmol/L. The difference between the results represents 0.0009 % which is considered not to be of any statistically significance. A statistically significant difference (p < 0.05) was recorded after three-minute recovery - following the inhalation of the hyperoxic gas mixture the average lactate level reached 8.53 (SD 2.82) mmol/L. This represented a decrease of 18.12 % while after inhaling the placebo the average lactate level equalled 9.06 (SD 2.98) mmol/L (a 13.4% decrease). Following the ten-minute recovery we observed the average lactate level of 6.65 (SD 2.31) mmol/L after the inhalation of the hyperoxic gas mixture (a 36.3% decrease compared to the values before the match). The average lactate level measured after the inhalation of placebo represented 7.73 (SD 2.39) mmol/L (a 25.86% decrease). We ascertained the statistical significance of the difference between the dynamics of lactate metabolism after the inhalation of the hyperoxic gas mixture and after inhaling air (p < 0.05). The inhalation of hyperoxic gas mixture before a match does not have a statistically significant effect on the lactate level after the load. However, the inhalation of hyperoxic gas mixture does significantly affect the dynamics of lactate metabolism in the third and 10th minute of the recovery time, based on the p < 0.05 level of statistical significance. Based on this result, we consider the inhalation of hyperoxic gas mixture an appropriate way to accelerate recovery time after a judo and karate match.